2021
DOI: 10.2147/ijgm.s321787
|View full text |Cite
|
Sign up to set email alerts
|

Leukapheresis and Hyperleukocytosis, Past and Future

Abstract: Hyperleukocytosis is a hematologic crisis caused by excessive proliferation of leukemic cells and has a relatively high early mortality due to a series of severe complications. Therefore, prompt and effective intervention is required. Leukapheresis performed using apheresis equipment to separate leukocytes from peripheral blood, at the same time returns autologous plasma, platelets and erythrocytes to the patient, is applied clinically for the treatment of hyperleukocytosis. Leukapheresis not only removes exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Future studies must evaluate lymphocyte removal in CCL patients using an extracorporeal device and determine the effectiveness of this method. In theory, antibody-directed lymphocyte reduction may be superior to standard leukapheresis in various states of hyperleukocytosis (not resulting in leukostasis in CLL) as the nanoparticles may be modified according to the patient’s leukocyte surface characteristics allowing for a targeted cell removal as opposed to an unspecific leukocyte depletion [ 15 , 16 ]. Furthermore, the generalizability and transferability of this method to target and remove specific cells in the blood, especially in other types of leukemia, where hyperleukocytosis often results in symptomatic leukostasis, is undoubtedly a strength of this method and opens new medical treatment approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies must evaluate lymphocyte removal in CCL patients using an extracorporeal device and determine the effectiveness of this method. In theory, antibody-directed lymphocyte reduction may be superior to standard leukapheresis in various states of hyperleukocytosis (not resulting in leukostasis in CLL) as the nanoparticles may be modified according to the patient’s leukocyte surface characteristics allowing for a targeted cell removal as opposed to an unspecific leukocyte depletion [ 15 , 16 ]. Furthermore, the generalizability and transferability of this method to target and remove specific cells in the blood, especially in other types of leukemia, where hyperleukocytosis often results in symptomatic leukostasis, is undoubtedly a strength of this method and opens new medical treatment approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The common uses include, but are not limited to, self-MNC preservation, component blood transfusion, etc. [ 26 ]. Several studies have validated and confirmed that DLA followed by conventional CTC capture technologies can significantly increase the CTC yield.…”
Section: Discussionmentioning
confidence: 99%
“…However, leukapheresis comes with high costs and requires specialized equipment, trained personnel, and need of a central venous catheter, which can cause a delay in treatment. Another disadvantage is the loss of red blood cell and platelets, so its suitability in patients with low Hb or platelets levels is limited [80]. However, we state that the disadvantages do not outweigh the benefits of leukapheresis.…”
Section: Discussionmentioning
confidence: 99%